Comparison of measured and calculated 40K activitiy per gram of K - Supian Bin Samat; Green, Stuart; Alun H. Beddoe (Universiti Kebangsaan Malaysia, 1997)
Measurement of the natural 40K body gamma-ray radioactivity via the whole-body counter (WBC) technique may yield the total body potassium (TBK) status, from which for example, the body cell mass can be derived (Moore et al. 1963). The accuracy of the derived TBK is of course critically dependent on the assumed value of the ratio 40K:TBK. Potassium chloride (KCI) has been widely used as the 40K calibration standard. In reviewing the literature (Burkinshaw 1967; Ross & Morris 1968; Havlik 1970, Young et al 1975; Manocha & Mohindra 1976; Holtzman 1977; Graham 1983; HMSO 1985-1986, Lykken et al 1987; Lan & Weng 1989; Fenwick et al. 1991), it is apparent that inconsistencies occur in the use of 40K activity per gram of natural potassium. It varies between 27.33 to 31.31 Bq per gram of potassium. The objectives of this study were to independently measure and calculate the 40K activity per gram of natural potassium in an attempt to reduce the uncertainty in the accepted figure. Experimentally the activity of 40K from a known amount of K was determined by measuring the 40K photon emission of an analar grade KCI sample solution and the absolute efficiency of the detection system at energy 1460 KeV. Both the photopeak count-rate and the absolute efficiency were measured using the gamma-ray spectroscopy technique. The 40K activity is also calculated from its half-life (IAEA 1989) and the number of atoms present in the sample. The measured and calculated values obtained were 30.18 ± 0.72 Bq g-1 and 31.00 ± 0.33 Bq g-1 respectively. The difference is of the order of 2.6%. The measured value is consistent with the literature values being close to the mean of the values, namely 29.77. In conclusion, it is believed that the experimental values reported in this work is one of the few experimentally determined results and it is reassuring to note that the experimental and theoretical values are in reasonable agreement.